The Correlation Between Self Care Diabetes on Foot Ulcer Risk in Diabetes Mellitus Clients - Selpina Embuai; Moomina Siauta; Hani Tuasikal (State Islamic University of Sunan Ampel, 2018)
Diabetes mellitus is one of the major causes of health problems and often occurs in almost every country (1). About 15% of all diabetics will have foot ulcers that are a serious complication and have an impact on amputations in the lower extremities (2). The rate of ulcers on the feet may occur over a five-year time span of 70% (3). The purpose of this study was to determine the relationship between self care diabetes on foot ulcer risk in clients with diabetes mellitus. The research design used was quasy experiment (pre-post test with control design). This research consists of 2 groups of intervention and control with each respondent as much as 47. Sampling technique with consecutive sampling. Instruments used monofilament 10 g neuropathy diabetic test Semmes-Weinstein monofilament type, 128 Hz tuning fork, foot care and leg exercises checklist form. The analysis used is paired t-test. There was relathionship between self care diabetes on foot ulcer risk with significance value is 0.00 (Î± <0.05). Diabetes self care is effective to prevent risk of foot ulcer in diabetes mellitus client.